INFORMATION SECURITY RISKS INVOLVING FUNSOFT AS A HEALTH MANAGEMENT INFORMATION SYSTEM - Halwenge, Peter Migoya; Liyala, S. O; Raburu, George (IJRDO -Journal of Computer Science Engineering, 2015)
This study looked at the various information security risks brought about by the implementationof funsoft which is a health management information system with a view of managing andmitigating the risks in a coherent and systematic manner. The study has used a positivistapproach with a research design that employed quantitative descriptive study of funsoft users andfocus group discussions with system administrators and records officers. The study populationwas eighty five with a sample size of forty six calculated using Yamane’s formula with aprecision of ten percent. The study reviewed current risk management practices used within theHMIS and IT in general and using a case study of three public hospitals in Kisumu county thatare at different implementation levels of funsoft, it further explored current potential obstaclesencountered in the implementation of systemic risk management strategy. This study finallyimplemented a strategy for managing risk within funsoft in a systematic and continuous mannerwhich was enriched by material documented in the literature. It was unearthed in the study thatall the three health facilities have no focal person to coordinate information security, lackpolicies and procedures on computer and information security and had never undertaken a riskassessment of the funsoft HMIS platform since its deployment.